The Relationship between Serum Anti Müllerian Hormone Level and Oocyte quality in In Vitro Fertilization Cycles - Fatemeh Keikha; Saeedeh Sarhadi; Farahnaz Farzaneh; Maryam Zamani (Mashhad University of Medical Sciences, 2022)
Introduction: The serum level of Anti Müllerian hormone (AMH) is a powerful test for predicting ovarian response that reflects not only the size of the primary follicle but also the quality of the oocytes. This study was conducted aimed to determine the relationship between serum AMH levels and the quality of oocytes obtained from IVF cycles in patients using IVF in Zahedan infertility center. Methods: This descriptive-analytical study was performed in 2017-2018 on 108 infertile women who were candidates for IVF in Zahedan. Patients were selected by census and entered the study. Patients' files were extracted and the necessary information such as age, oocytes quality and serum AMH levels were extracted and recorded in the patient's information form. Data were analyzed by SPSS software (version 19) and Chi-Square test and ANOVA. P< 0.05 was considered statistically significant. Results: The mean serum AMH level of patients was 3.81 ± 3.26 ng/ml. 87 patients (80.6%) had oocyte quality (A), 80 patients (74.1%) had B quality, 34 patients (31.5%) had C quality and one patient (0.9%) had D quality. The mean age was not significantly associated with serum AMH levels and oocytes quality (P> 0.05). Conclusions: AMH levels are associated with oocyte quality in IVF cycles, while age was not associated with AMH levels and oocyte quality. Therefore, AMH levels are an indicator of the quality of oocyte in IVF cycles.